Agricultural knowledge and information system: Lessons lerand in the postsocialist period in Romania and Bulgaria - Marioara Rusu; Violeta Dirimanova; Violeta Maria Simionescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
The new challenges facing Eastern European rural and agricultural sector impose, among other things, a review of the links between knowledge production and its use to promote innovation. Given that, agriculture is the main source of livelihood for a large part of the rural population in Romania and Bulgaria and its development requires multiple interventions that include, inter alia, ensuring effective transfer of agricultural modern knowledge, technologies, methods and practices to the direct beneficiaries - farmers. Both in Romania and Bulgaria, agricultural knowledge generation (research), transfer (extension) and use (farmers as end users) passed during the post-socialist period through important changes. The main objective of this paper is to analyze the Agricultural Knowledge and Information System (AKIS), in the two countries, in terms of pursued objectives, structure and performed functions. Based on this analysis the authors synthesize the main lessons learned during the post-socialist period in the two countries, and outline the future direction of development of agricultural knowledge, production, transfer and use them in agreement with European requirements.
Keywords: 330; AKIS; agricultural extension; agricultural research and education; Romania; Bulgaria